Characteristic of food waste gasification in supercritical water for hydrogen production. (August 2022) - Cao, Wen; Wei, Yimeng; Jin, Hui; Liu, Shi; Li, Linhu; wei, Wenwen; Guo, Liejin
Abstract: In this work, an experimental study was done in an autoclave reactor to evaluate the gasification characteristics of food waste in supercritical water. The effects of reaction temperature (550–700 °C), residence time (0–30 min), feedstock concentration (5 wt%-9 wt.%), catalyst type (K2 CO3, Na2 CO3, and Raney-Ni), and catalyst loading (Catalyst/dry feedstock 0.5–2) on gas production and liquid products were investigated. The results indicated that higher reaction temperature and longer residence time positively promoted food waste gasification. The organic compound species in liquid products decreased quickly to form gas products with the increased temperature, and the aromatic compounds were the key organic matter for the complete gasification of food waste. The addition of catalysts could significantly convert more liquid intermediates into gaseous products, and improve the gasification performance of food waste. The catalytic performance of catalysts can be ranked as K2 CO3 > Raney-Ni > Na2 CO3 . H2 yield and carbon gasification efficiency increased with the increase of K2 CO3 loading, reaching the highest values of 38.29 mol kg −1 and 95.84% with the addition of 14 wt% K2 CO3, respectively. This work indicated that food waste could be well treated and utilized as an energy resource to produce H2 by SCWG technology. Graphical abstract: Image 1 Highlights: Supercritical water gasification of food waste was studied in a high heating rate autoclave reactor. Higher reaction temperature and longer residence time could significantly enhance H2 production. The maximum H2 yield and CE reached 38.29 mol/kg and 95.84% at 650 °C with 14 wt% K2 CO3 . Catalysts could significantly improve the conversion of liquid intermediates into gaseous products.